Pengaruh Permainan Ular Tangga Terhadap Hasil Belajar Matematika Siswa Kelas IV di SDN 51 Kota Bengkulu - Lisa Apriyanti; Ansyori Gunawan; Feri Noperman (JURIDIKDAS, 2019)
This study aims to determine the effect of the snake ladder game on the learning outcomes of Mathematics students of class IV in SD Negeri 51 Kota Bengkulu. This type of research is a quantitative. The research design used was Quasi Eksperimen with the type of design The Matching Only Pretest-Posttest Control Group Design, where the test taking twice before and after given treatment on the sample class. The population in this research is all the fourth grade students in SDN bengkulu city. The sampling technique using Cluster Random Sampling, the sample in this research is the students of grade IV B and IV A SD Negeri 51 Kota Bengkulu. The research instrument used in the form of test result of learning in the form of essay given through pretest and posttest. The results were analyzed by using descriptive analysis and inferential analysis that is t-test. The results showed that the mean posttest in experimental group was 68.92 and the control group was 50.43. The result of posttest-t test in control group with experiment showed that tcount of 2,263 is bigger than t value of table at 5% significant level 2,011, so Ha is accepted and Ho is rejected. This means that there is a ladder snake effect on the results of learning mathematics students of class IV in SD Negeri 51 Kota Bengkulu.